High detectability with low impact: Optimizing large PIT tracking systems for cave‐dwelling bats. Issue 19 (15th September 2019) - van Harten, Emmi; Reardon, Terry; Lumsden, Lindy F.; Meyers, Noel; Prowse, Thomas A. A.; Weyland, John; Lawrence, Ruth
Abstract: Passive integrated transponder (PIT) tag technology permits the "resighting" of animals tagged for ecological research without the need for physical re‐trapping. Whilst this is effective if animals pass within centimeters of tag readers, short‐distance detection capabilities have prevented the use of this technology with many species. To address this problem, we optimized a large (15 m long) flexible antenna system to provide a c . 8 m 2 vertical detection plane for detecting animals in flight. We installed antennas at two roosting caves, including the primary maternity cave, of the critically endangered southern bent‐winged bat ( Miniopterus orianae bassanii ) in south‐eastern Australia. Testing of these systems indicated PIT‐tags could be detected up to 105 cm either side of the antenna plane. Over the course of a three‐year study, we subcutaneously PIT‐tagged 2, 966 bats and logged over 1.4 million unique detections, with 97% of tagged bats detected at least once. The probability of encountering a tagged bat decreased with increasing environmental "noise" (unwanted signal) perceived by the system. During the study, we mitigated initial high noise levels by earthing both systems, which contributed to an increase in daily detection probability (based on the proportion of individuals known to be alive that were detected each day) from <0.2 (noise level ≥30%) to 0.7–0.8 (noise level 5%–15%). Conditional on a low (5%) noise level, model‐based estimates of daily encounter probability were highest (>0.8) during peak breeding season when both female and male southern bent‐winged bats congregate at the maternity cave. In this paper, we detail the methods employed and make methodological recommendations for future wildlife research using large antennas, including earthing systems as standard protocol and quantifying noise metrics as a covariate influencing the probability of detection in subsequent analyses. Our results demonstrate that large PIT antennas can be used successfully to detect small volant species, extending the scope of PIT technology and enabling a much broader range of wildlife species to be studied using this approach. Abstract : Passive integrated transponder tag (PIT) technology permits the "resighting" of animals tagged for ecological research without the need for physical re‐trapping; however, short‐distance detection capabilities of antennas have prevented the use of this technology with many species. In a three‐year study, we optimized a large 15 m loop antenna to detect animals in flight, subcutaneously PIT‐tagged 2, 996 cave‐dwelling bats, and logged over 1.4 million detections, with 97% of the tagged individuals being detected at least once. Results demonstrate that large PIT antennas can successfully be used to detect small volant species, extending the scope of PIT technology and enabling a much broader range of wildlife species to be studied using this approach.